The Influence of Probiotic Administration on the Performance of Laying Hens - Bentangkoesoemah, R R F; Dudi, D; Hernaman, I (Politeknik Negeri Lampung, 2025)
This study aims to evaluate the effects of probiotic administration on the performance of laying hens. The research method involves two groups of laying hens kept under the same conditions, with one group receiving probiotic supplementation and the control group receiving standard feed. Parameters observed include egg production rate, egg weight, mortality rate, and overall health. Statistical analysis (t-test, p < 0.05) indicates significant differences between groups. The results suggest probiotics enhance productivity and health, with economic benefits for farmers.